الأبعاد التربوية في قصة موسى مع بني إسرائيل في سورة الأعراف : دراسة تحليلية من خلال تفسير الشعراوي - Pohan, Marhamah (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
The purpose of this study is to explore educational dimensions of the story of Prophet Moses (peace be upon him) with Bani Israel in Surah Al-A'raf based on Shaykh Sha'rawi's interpretation. This study intends to analyze Shaykh Sha'rawi's thoughts on the issue. Besides, the research attempts to examine the story of Bani Israel and Moses as reflected in Surah Al-A'raf, and to study their misbehavior towards Prophet Moses as well as to reveal the educational context from the story such as tawhidic (asserting the oneness of God), da'wah (the act of inviting or calling people to practice God's messages), and social dimension. The methodology used in this research is the inductive and analytical approach. The inductive approach is used in collecting the Qur'anic verses about Moses's story with Bani Israel in Surah Al-A'raf, in the hadiths, and the historical facts. Besides, this study also employed the analytical approach which is used to investigate the educational dimensions in the story of Moses with the Bani Israel, and their characteristics as reflected in Sūrah Al-A'raf, through the tafsir of Shaikh Shaykh Sha'rawi and the books from various commentators. The results of the study revealed that Shaykh Sha'rawi has made a profound influence for the Muslims around the world and improved the way of their thinking with his scholarly studies. He is regarded to be one of the prominent preachers and a revolutionary mind of this century. His tafsir includes an educational and a sociological interpretation. Furthermore, the story of Moses with Bani Israel in Sūrah Al-A'raf contains the message of Moses (peace be upon him), to rescue Bani Israel from the persecution of the Pharaoh and deliver them from Egypt to the blessed land (Palestine) that Allah SWT granted for them. This study concludes that viewed from educational point of view, the story of Moses with Bani Israel in Surah Al-A'raf seen from Shaykh Sha'rawi 's interpretation consist of three dimensions, including the tawhidic (asserting the oneness of God), the da'wah (the act of inviting or calling people to practice God's messages), and the social dimensions.